Experiments in basic chemistry - Murov, Steven L. (John Wiley & Sons, 1997)
This outstanding lab book uses an exploratory approach which encourages students to inquire and discover concepts as they experiment. The interesting and challenging experiments have been selected to maximize educational impact while minimizing hazards and cost. In this edition the "Prelaboratory Exercises" have been extensively expanded and printed on isolated pages so that they can be torn out and handed in without disturbing the "Procedure" section. Numerous new questions have been added to provide a much stronger connection between the lecture and lab portions of the course. A new feature, "Chemical Capsules," presents provocative subjects to stimulate interest and discussion.